A Study of the Systems of Jewels in the Prohibitions and Orders of Sheikh Mohammed bin Saif Al- Atiki: Jurisprudence of Zakat - Al Mazrouei, Hamad Yousef Ibrahim (Dirasat: Shari'a and Law Sciences, 2021)
This research discusses Naẓm Alǧwāhir fi Alnawāhy Wālāmwāmir by Sheikh Mohammed bin Saif al-Atiku. The first section defines the terminology used in the research, presents a brief biography of the poet, and then concludes by proving the attribution of the poetry to its poet and showed the errors in its attribution to others. The first section also displays some samples of the copies of the manuscripts used in the study, with a description and matching of their texts. In the second section, I begin with a description of the vocabulary and chapters of the entire poetry to be discussed. Then I mention the verses with the investigation and the difference between written versions and influential words. The section concludes by proving some commentary and explanation of the verses related to the provisions of Zakat and clarifying the provisions of Zakat contained in the mentioned verses by inferring them from the Hanbali references. I conclude the research by highlighting the results and recommendations. One of the most important results was to prove the validity of the attribution of the poetry to Sheikh Muhammad bin Saif Al-Ateeqi and to clarify the jurisprudence provisions contained in the verses according to the doctrine of the poet, which is the Hanbali School. As for the most important recommendations: paying attention to the heritage of scholars and working to revive it, especially concerning jurisprudence systems.